The Meiji Secret: The Emergence of Zaibatsu Dominance in Japan - Ramirez, Marcus (University of Wisconsin--Stout. Office of Research and Sponsored Programs, 2019)
This paper examines how the intervention of American sailors in Japanese politics created a dramatic social shift in Japan freeing Japanese merchants to begin building corporate enterprises. These corporate enterprises became subsidized by the government, expanded rapidly, and eventually became capable of influencing the government on its path to WWII. The control these companies exerted over the Japanese through their control over the economy was extensive. So pervasive were these companies that dissolution was near impossible without collapsing the Japanese economy, to this day many survive and thrive well beyond the Japanese borders.
Keywords: Industrialization; World War, 1939-1945; Japan